Congenital heart defect - aortopulmonary window: diagnostic features in infants - A.A. Malska; O.B. Kuryliak; T.A. Yalynska; O.V. Stogova (Zaslavsky O.Yu., 2023)
Aortopulmonary window (APW) is a congenital heart defect characterized by the presence of an abnormal connection between the pulmonary artery and the proximal part of the aortic arch directly above the level of the semilunar valves. It is one of the rarest cardiac defects (frequency of 0.2-0.6 %). APW occurs as an isolated cardiac lesion or in association with other anomalies such as coarctation of the aorta, interrupted aortic arch, tetralogy of Fallot, and atrial septal defect or patent ductus arteriosus. Treatment of APW comprises surgical correction of the defect, which should be performed immediately after diagnosis in order to prevent the development of pulmonary hypertension. Postoperative complications after surgical correction of APW occur rarely and depend on the association of this defect with other congenital heart defects, especially with an interrupted aortic arch. In this article, we present a retrospective analysis of patients with APW for 2003-2022, who were examined at the Lviv Regional Children's Hospital OHMATDYT, and 2 clinical cases of APW in 2- and 10-month-old boys.